SEGMENTATION AND GRAIN SIZE OF CERAMICS - Arnould, Xavier; Coster, Michel; Chermant, Jean-Louis; Chermant, Liliane; Chartier, Thierry; Elmoataz, Abder (Image Analysis and Stereology, 2011)
This paper presents some methods to automatically extract the grain boundaries of materials in order to develop an automatic method to determine the grain size and morphological parameters of ceramic materials. Results are presented in the case of sintered cerine (CeO2) materials.